(3JMaI GdHQQI aj GdeSGFd GdYTQI aj GdJUhas - (3TQa GdHZOGOj , TQa Hf eDjO, eLOGdOjf CHh SYjO,J (B616 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYde TYGQ Cgd GdgOi CeG HYO aEf JaVd GdfGS HYO GdEfHjGA GdcQGe CFeI GdgOi s
(3BNQgG (B:s
(3heffaQOjf Yfge HHhGWfge hCf cGfhG eY LdSGFge fWhGgQge bGd GdTjN QVi Gddg Yfg agPG eG SeM Hg GdhbJ Je GdcJGH s
(3HGdfSNI CNWGA ai GdVHWcJH GdcJGH HCeQ ef GdTjN fhQ GdOjf Ydi Hf TQa GdOjf jMji GddLei GdUhai GdYQGbis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B297s
Keywords: (3GdJUha hGdBOGH GdTQYjIs